Development and validation of a nomogram for predicting postoperative pulmonary complications in older patients undergoing noncardiac thoracic surgery: a prospective, bicentric cohort study - Yongxin Zhou; Haiyan Wang; Dianyu Lu; Tao Jiang; Zhanpeng Huang; Feixiang Wang; Yonghua Yao; Yu Gu; Wei Wei (BMC Geriatrics)
Abstract Background The ARISCAT score, a prospectively developed generic classification for postoperative pulmonary complications (PPCs), has shown excellent predictive performance in general surgery. However, there is no reliable classification instrument for PPCs prediciton in thoracic surgery. Objective This study aimed to develop and validate a novel nomogram for estimating the risk of pulmonary complications in older patients (≥ 65 years) within 30 days after NCTS. Methods A nomogram was developed using predefined candidate predictors of 30-day PPCs. It was fitted with least absolute shrinkage and selection operator and logistic regression methods. Internal validation was performed using a bootstrap-resampling approach, while external validation used an independent, temporally separated cohort. The model’s performance was assessed based on its discriminative potential (area under the receiver operating characteristic curve [AUC]), predictive ability (calibration plots), and clinical utility (net benefit). Results In the development (n = 1449) and validation (n = 449) cohorts, 34.9% and 31.4% of patients, respectively, developed pulmonary complications 30 days post-surgery. The final nomogram incorporated eight predictors (age, surgical approach, desaturation of < 92% for more than 2 min, duration of surgery, smoking status, FEV1/FVC%, respiratory infection in the last 30 days, and neoadjuvant chemotherapy). The nomogram showed excellent discrimination (AUC = 0.866, 95% confidence interval [CI], 0.846–0.885), calibration (Hosmer- Lemeshow test, P = 0.97) and overall performance (Brier score = 0.014) in the development cohort. Similar results were observed in the external validation cohort (AUC = 0.825, 95% CI, 0.786–0.864). A decision curve analysis indicated that the nomogram offers a positive net benefit compared with the ARISCAT and LAS VEGAS scores. Conclusions This novel nomogram can reliably identify older patients with a high risk for pulmonary complications within 30 days after NCTS. Trial registration ChiCTR2100051170.